Dietary Patterns in Pregnancy and Infants\\\' Anthropometric Parameters at Birth - Majid Mohammadshahi; Mehrnoush Zakerzadeh; Samira Hashemi; Fatemeh Haidari (Tehran University of Medical Sciences, 2013)
Background & Aim: There is little information regarding relationship between maternal dietary pattern and infant anthropometric parameters at birth. This study was carried out to determine relationship between dietary patterns in pregnancy with infants' anthropometric parameters .   Methods & Materials: In this cross-sectional study, 94 pregnant women (GA: 37-40 weeks) referred to Ahvaz Razi hospital were selected. Anthropometric parameters were measured. The dietary intakes were assessed using a semi-quantitative food frequency questionnaire. Factor analysis was used to identify dietary patterns. Statistical analysis was done in the SPSS.   Results: In this study, three major dietary patterns including "healthy", "traditional" and "western" dietary patterns were identified. After adjusting of confounders (age, physical activity, energy intake, pregnancy weight gain and infant sex), the relationship between dietary patterns with birth weight, height and head circumference were exhibited in three models. The relationship between healthy dietary pattern and infant weight, height and head circumference at birth was significantly positive in all models (P<0.05). Western dietary pattern had significant negative relationship with head circumference in the model 1 and 2. Moreover, it had negative relationship with birth weight in the model 1 (P<0.05). Traditional dietary pattern did not show any significant relationship with anthropometric parameters at birth.   Conclusion: The present study found significant relationship between maternal dietary patterns with anthropometric parameters at birth. Further prospective studies are suggested to confirm the findings.